Risk behaviors after kidney transplant that influence the adherence to treatment (Research, Society and Development, 2022)
The objectives of the study were to identify the main risk behaviors of post-transplant chronic kidney patients and to relate these behaviors to the outcome of non-adherence. Method: This was an observational, descriptive, retrospective, cross-sectional study with a quantitative approach, whose sample consisted of medical records of post-kidney transplant patients who had at least one nursing consultation at the post-transplant clinic in a university hospital located in the state of Rio de Janeiro, from August 2016 to December 2020. The analysis was performed from the data collected, using the Statistical Package for Social Sciences - (SPSS), version 24.0, for Windows. Results: Ninety-eight medical records were evaluated, and significant rates were identified in the following behaviors: failure to follow the diet (30.5%), delay or forgetfulness in the use of medications (17.9%), alcoholism (8.4%), hygiene inadequate (1.1%), smoking (1.1%), recurrent urinary tract infection (1.1%), irregular use of sunscreen (1.1%), increased creatinine (1.1%) and sedentary lifestyle (1.1%). Conclusion: In this study, it was possible to identify problems in the established therapy and, consequently, the presence of risk behaviors after kidney transplantation, which may influence the survival of the transplanted graft. Nursing can and should act to strengthen the self-care of these patients aiming at the possibility of a better therapeutic response.